2017
DOI: 10.1002/ejoc.201700374
|View full text |Cite
|
Sign up to set email alerts
|

A Mild and Chemoselective Hydrosilylation of α‐Keto Amides by Using a Cs2CO3/PMHS/2‐MeTHF System

Abstract: A Cs2CO3‐catalyzed hydrosilylation reaction of α‐keto amides that proceeds through the in situ formation of MeSiH3 has been developed by using inexpensive polymethylhydrosiloxane in 2‐methyltetrahydrofuran (2‐MeTHF) as the solvent. A wide range of aryl and alkyl α‐keto amides, prepared from anilines and alkylamines, were subjected to the hydrosilylation conditions to afford α‐hydroxy amides in moderate to excellent yields. This transition‐metal‐free protocol was applied to a chemoselective hydrosilylation, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…What is more, 2-methyltetrahydrofuran was used as the solvent in exchange for a carcinogen 1,4dioxane (Scheme 7). 73 Subsequently, Ding et al exploited the KOH-catalyzed system for the reduction of cyclic imides (Scheme 8). 74 Upon the investigation of the reaction scope, several ω-hydroxylactams and aryl lactams were obtained in quite good yields, utilizing PMHS or Ph 2 SiH 2 as reducing agents.…”
Section: Hydrosilylation Of Unsaturated Carbon-heteroatom (O N) Moiementioning
confidence: 99%
“…What is more, 2-methyltetrahydrofuran was used as the solvent in exchange for a carcinogen 1,4dioxane (Scheme 7). 73 Subsequently, Ding et al exploited the KOH-catalyzed system for the reduction of cyclic imides (Scheme 8). 74 Upon the investigation of the reaction scope, several ω-hydroxylactams and aryl lactams were obtained in quite good yields, utilizing PMHS or Ph 2 SiH 2 as reducing agents.…”
Section: Hydrosilylation Of Unsaturated Carbon-heteroatom (O N) Moiementioning
confidence: 99%
“…Polymethylhydrosiloxane (PMHS) is an attractive H-donor among commercially available hydrosilanes, which can be attributed to its unique character, which is inexpensive, commercially available, non-toxic, biodegradable, and stable in air and moisture (Volkov et al, 2015). In addition, PMHS is soluble in most organic solvents due to its low viscosity (Kumar et al, 2017). Based on these findings, Long et al (2019) depicted a benign method to effectively catalyze the reduction of FF to FFA over commercially available Cs 2 CO 3 utilizing non-toxic and cheap PMHS as a hydrogen source, giving an excellent FFA yield of 99% (Table 4, entry 2).…”
Section: Catalytic Hydrogenation Of Biofuranic Aldehydes To Alcoholsmentioning
confidence: 99%
“…These results indicated that both cations and anions played a crucial role in the reaction. With the increase of the cation radius, the salt ionic property increased, thus showing enhanced solubility [47]. Among the alkali/alkaline earth metals, K + (with a relatively larger ionic radius) allows the paired carbonate to be more freely available to contact the hydrosilane and substrate.…”
Section: Effect Of Different Catalystsmentioning
confidence: 99%
“…Apart from the cation, the influence of the anion on the reaction is not negligible, mainly with respect to its basicity that has a positive correlation with nucleophilicity. In this regard, carbonate with good accessibility and relatively high nucleophilicity is more prone to attack and activate the silane, Ph 2 SiH 2 , to release hydride [47]. In view of the superior BHMF yield, K 2 CO 3 was chosen as the optimized catalyst for the reduction process.…”
Section: Effect Of Different Catalystsmentioning
confidence: 99%